2019
DOI: 10.1038/s41419-019-1718-7
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 is essential for HMGB1-mediated post-myocardial infarction tissue repair through affecting apoptosis, cardiac healing, and angiogenesis

Abstract: The poor prognosis of patients with acute myocardial infarction is partially attributed to a large number of cardiomyocyte apoptosis, necrosis, limited cardiac healing and angiogenesis, and cardiac dysfunction. Immune cells dysfunction leads to nonhealing or poor healing of wounds after acute myocardial infarction. Toll-like receptor 9 (TLR9) as an essential part of the innate immune system plays a vital role in regulating cardiomyocyte survival and wound healing. During hypoxia, High Mobility Group Box 1 (HMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 45 publications
1
47
1
Order By: Relevance
“…Recently, it was shown that TLR5 inhibition ameliorates cardiac fibrosis by modulating inflammation and tissues' remodeling (Liu et al, 2015). Other studies determined that HMGB1 blockade alleviates myocardial fibrosis (Wang et al, 2014), possibly interfering with the TLR2-HMGB1 ligand and cardiac autophagy (Wu et al, 2018;Liu et al, 2019). Consistent with these evidences, we demonstrated that mdx cardiac dysfunctions could be partly due to an inflammatory signaling pathway in which PTX3 is involved together with S100β, HMGB1, TLR5, and TLR9, with consequent increment of collagen deposition and fibrosis.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, it was shown that TLR5 inhibition ameliorates cardiac fibrosis by modulating inflammation and tissues' remodeling (Liu et al, 2015). Other studies determined that HMGB1 blockade alleviates myocardial fibrosis (Wang et al, 2014), possibly interfering with the TLR2-HMGB1 ligand and cardiac autophagy (Wu et al, 2018;Liu et al, 2019). Consistent with these evidences, we demonstrated that mdx cardiac dysfunctions could be partly due to an inflammatory signaling pathway in which PTX3 is involved together with S100β, HMGB1, TLR5, and TLR9, with consequent increment of collagen deposition and fibrosis.…”
Section: Discussionsupporting
confidence: 86%
“…TLR7 deficiency suppresses the cardiac remodeling process induced by myocardial infarction 37 . TLR9 is essential in the pathology of the cardiac remodeling process postmyocardial infarction 38 . In our experiment, we observed an increased level of TLR4, and TLR7, and a decreased level of TLR9 expression in hypertrophic cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TLR9 also showed to contribute to the inflammatory response following MI in a mouse model through stimulation by HMGB-1 and mtDNA (12). However, a contrary report observed that TLR9-HMGB-1 was essential for survival of cells, wound healing and angiogenesis in a model with a longer follow-up (13). Experimental studies investigation the role of TLR5 were also performed and it is expressed in the hearts of mice, rats and humans (152).…”
Section: Other Tlrsmentioning
confidence: 99%